Comparative study of phytochemicals and antioxidant potential of wild edible mushroom caps and stipes - Ribeiro, Bárbara (2008)
A comparative study of the organic acids and phenolics composition and of the total alkaloids content of entire wild edible mushrooms (Russula cyanoxantha, Amanita rubescens, Suillus granulatus and Boletus edulis) and correspondent caps and stipes was performed. All species presented oxalic, citric, malic and fumaric acids, with A. rubescens exhibiting the highest total organic acids content. Organic acids were preferably fixed in the cap. Among phenolics, only p-hydroxybenzoic acid was found in A. rubescens and S. granulatus, in very low amounts. B. edulis was the species that presented the highest total alkaloid amounts. Except for this species, alkaloids mainly accumulated in the cap. All of the species exhibited a concentration-dependent scavenging ability against DPPH . B. edulis revealed the highest antioxidant capacity. The cap seemed to be the part with highest antioxidant potential. Some relationships between chemical composition and antioxidant capacity were considered